Aesthetic Subjectification Through Ambivalent Play: Exploring a Ludic Theory of Popular Propaganda - Zou, Sheng (The Journal of communication inquiry, 2022)
Propaganda research was central to the coalescence of communication studies into a modern social science field in the early twentieth century. Positivist and behaviorist in its orientation, traditional propaganda research centers on questions of message and effect, brushing aside the culturally rich forms that propaganda assumes as well as the myriad ways in which subjects experience these forms on an aesthetic and sensorial level. This article endeavors to complement the message-and-effect-centric orientation by proposing a (re)turn toward the aesthetic dimension of propaganda, with a particular emphasis upon the nexus between propaganda and the concept of play. Drawing on observations from modern China, I venture a ludic theory of popular propaganda that captures the affective, non-discursive, and post-ideological dimensions of propaganda artifacts as well as subjects' aesthetic engagement with them. My intent in this article is to diversify the perspectives, approaches, and possibilities of propaganda research within the field of communication and media studies.